Propriedades adesivas de compósitos de matriz epóxi reforçado com liga quasicristalina - Altidis, Jaqueline Dias (2013)
In recent years, the constant need for new materials lead to the development of new composite materials. The composites based on epoxy resin reinforced with alloy quasicrystalline, they bring excellent tribological properties as high hardness and wear resistance. The quasicrystals are materials with different microstructural characteristics: They are aperiodic, but with the long-range ordering. These microstructural characteristics quasicrystalline materials exhibit exceptional mechanical properties and surface, such as high hardness, low surface energy, low friction coefficient, good resistance to oxidation and corrosion, has low electrical and thermal conductivities. Despite striking surface properties already mentioned, these alloys retain high adhesiveness and low brittleness. This factor compromises its use both for applications requiring the mechanical tensile and bending. Thus, the development of composites using quasicrystalline materials as reinforcement and epoxy matrix, it is found an alternative to the use of the important features. For this study were developed matrix composites reinforced epoxy alloy powder quasicrystalline Al62,2 Cu25,5 Fe12,3 comparing the composites produced with the same matrix with aluminum powder, copper powder and iron powder. To evaluate the adhesion strength of the composites, bonded joints was subjected to shear testing, using reinforced epoxy composite metal powders in various ratios of volume of reinforcement. Quasicrystal reinforced composites for certain volume ratios there was an increase in adhesive properties compared to the pure epoxy. It was observed that the quantities and the elements constituting the alloy quasicrystalline influence the adhesive properties.